Terahertz Light-Field Imaging With Silicon Technologies - U. R. Pfeiffer; A. Kutaish (IEEE Open Journal of the Solid-State Circuits Society)
The terahertz (THz) frequency range is widely considered the most challenging and underdeveloped frequency range due to the lack of technologies to effectively bridge the transition region between microwaves (below 100 GHz) and optics (above 10 000 GHz). Although THz radiation would be perfect for material identification and as a safe alternative to X-rays for producing high-resolution images of the interior of opaque objects, first a fundamentally new approach is needed to establish novel devices and techniques.